Assessment of Spiritual Health and Well-Being of Psychiaric Nurses in a Mental Health Hospital - Maria Frani Ayu Andari Dias (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
The practice of mental health care performed by nurses in mental hospitals requires nurses to also provide spiritual care. Nurses who have a healthy spiritual state can certainly provide good spiritual care to their patient. Unfortunately, nurses admit that in practice, this spiritual element is often overlooked and not considered important in practice. This study aims to examine the health and spiritual well-being of mental health nurses working in mental health care facilities (hospital based). This research was a pilot study using Mix Method (MM), the design of this study was a sequential research design (Qual-Quant) between quantitative and qualitative study. Data collection was carried out using a self-administered survey and using the SHALOM (Spiritual Health and life orientation measure) instrument from Fisher which had a total of 22 questions. Quantitative data analysis was performed using descriptive statistics, while qualitatively, the data were analyzed using the thematic analysis method. A total of 22 mental health nurses participated in this research project. This number represents the nurses who work in all wards in mental hospitals. Researchers used the cluster sampling method to select participants who were given questionnaires and the snowball sampling method to find suitable informants to be interviewed. This research shows nurses expressing worship of the Creator (Mean = 4.54, SD = 0.59) as the most important thing in the ideal standard of health and spiritual well-being. Likewise, with daily life and practice (Mean = 3.81, SD = 1.68). Nurses assess their health and spiritual well-being were more determined by the transcendental domain, especially with religious rituals. This study concluded that nurses have a well-distributed state of health and spiritual well-being ranging from the personal domain to transcendence, with dominance in the transcendence domain.